Shadow of Your Former Self: Exploring Project Leaders’ Post-Failure Behaviors (Resilience, Self-Esteem and Self-Efficacy) in High-Tech Startup Projects - Umer Zaman (MDPI AG, 2021)
Globally, demands for sustainable strategies in the ICT industry have attracted greater momentum as high-tech projects continue to fail in large numbers. Recent studies have underpinned project resilience as a major factor for overcoming these increasing project failures, delays, or termination. However, the complex behaviors of resilient project leaders, especially in post-failure conditions, have been largely overlooked. To address this critical research gap, the present study identifies the direct relationships between three potential behavioral traits of project leaders (i.e., resilience, self-esteem, and self-efficacy) and examines how they move forward beyond project failures. The present study also explored whether self-esteem mediates project leaders’ resilience and self-efficacy. Drawing on data from 232 project leaders in Pakistan’s high-tech start-ups, the new findings suggest that there are significant positive effects of project leaders’ resilience and self-esteem on their self-efficacy, and that project leaders’ resilience and self-efficacy is significantly mediated by their self-esteem. As the project resilience theory gains traction, the present study findings have pinpointed major steps for meeting project challenges ahead of time, allowing leaders and teams to learn from failures, and also for improving organisations’ ability to implement successful and sustainable high-tech projects especially in emerging economies.